Clinical accuracy of Dexcom G6 and G7 continuous glucose monitors in hospitalized pediatric patients with type 1 diabetes: a real-world study - Dong Jun Ha; Hakyung Lee; Jeongho Han; Mi Yang; Hwa Young Kim; Jaehyun Kim (Annals of Pediatric Endocrinology & Metabolism, 2026)
Purpose: Continuous glucose monitoring (CGM) is increasingly being used in inpatient pediatric diabetes care; however, data on its real-world accuracy remain limited.Methods: We retrospectively assessed the clinical accuracy of factory-calibrated Dexcom G6 and G7 CGM systems in 69 pediatric patients with type 1 diabetes at a Korean tertiary hospital between 2019 and 2025. A total of 1,838 CGM readings were temporally paired with point-of-care (POC) capillary glucose measurements. Accuracy was evaluated using the mean absolute relative difference (MARD), mean absolute difference (MAD), Bland-Altman analysis, and Clarke error grid classification. Subgroup analyses were performed according to wear day, glucose range, care setting, and CGM type.Results: The overall MARD was 10.6%±10.1% and MAD was 15.4±16.2 mg/dL. Accuracy improved over time, with MARD declining from 13.8% (G6) and 11.0% (G7) on day 1 to